PENGGUNAAN TEPUNG GARUT DAN AREN SEBAGAI PAKAN BUATAN UNTUK PEMELIHARAAN SERANGGA HAMA TEMBAKAU Helicoverpa assulta (GuenÃ©e.) (Lepidoptera: Noctuidae) PADA SKALA LABORATORIUM - , Siami Sitatin, S. Si; , Dr. siti Sumarmi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The oriental tobacco budwrom, H. assulta is one of the important insect pests of tobacco plant. Rearing of H. assulta was conducted in the laboratory. This be caused the insect can be used as model animal in the study of physiology, ecology, genetics and biological control programs. The aims of rearing H.assulta were to determine the effect of the three types of the artificial diets to the survivorship, pupal weight and its fecundities. This reaserch used Complete Randomized Design (CRD) method with two treatments groups (arrowroot and sugar palm starch) diets and an agar diet for a control treatment. Sixty larvae were used for each treatment. The survivorship and fecundity of H. assulta observed for two generations. The data was analyzed by statistic method ANOVA and DMRT (Duncan Multiple Range Test) was used. The results showed that the fastest of an average of a life cycle of H. assulta was completed in 41,55 days on agar diet and the longest one was on a garut starch diet (48,37 d). The highest of the survivorship of H. assulta on the second generation was in the sugar palm starch diet (71,67%) and the lowest of survivorship of H. assulta was on arrowroot starch diet (8,33%), whereas the survivorship of H. assulta on the third generation for both treatments were not significants with the control treatment. The highest of the fecundity of H. assulta was obtained arrowroot starch diet (81,11%) and the lowest of the fecundity of H. assulta was in sugar palm starch diet (6,98%). The pupal weight of the second generation and the third generation of H. assulta reared on the three kinds of the artificial diets was not significantly differents. The conclusion of this reaserch is the arrowroot and sugar palm starch diets can be used as an artificial diet for rearing H. assulta. The agar diet was the fastest period of the life cycle. The palm sugar starch diet was good for the survivorship. The arrowroot starch diet was good for fecundity of the insect. The pupal weight of the insect was relatively similar on the three different type of the insect diet.